Advances in materials and mechanical engineering select proceedings of ICFTMME 2020,Ghaziabad, Uttar Pradesh, India - Pandey, Chandan; Goyat, Vikas; Goel, Sunkulp (Singapore Springer, 2021)
This book presents the select proceedings of 1st International Conference on Future Trends in Materials and Mechanical Engineering (ICFTMME-2020), organised by Mechanical Engineering Department, SRM Institute of Science and Technology (Formerly known as SRM University), Delhi-NCR Campus, Ghaziabad, Uttar Pradesh, India. The book provides a deep insight of future trends in the advancement of materials and mechanical engineering. A broad range of topics and issues in material development and modern mechanical engineering are covered including polymers, nanomaterials, magnetic materials, fiber composites, stress analysis, design of mechanical components, theoretical and applied mechanics, tribology, solar, additive manufacturing and many more. This book will prove its worth to a broad readership of engineering students, researchers, and professionals.
Synthesis and Stability of Al2O3/ Water Nanofluids -- Enhanced Electrocatalytic Activity of Poly (trans- 2, 3-Dimethyacrylic acid) Modified Electrode for Hydrazine Sensing -- Effect of Temperature on the Sliding Wear Behavior of HVOF Sprayed Al2O3 Composite Coating -- Engine Friction Reduction using Cu Nanofluid as Lubricant -- Review of Transformer Core and Winding Design with Material Used -- Develop an Al-alloy for High Pressure-high Temperature Applications by Enhancing Thermo-mechanical Properties -- A Review on Mechanical Properties of Bamboo Fiber-based Composites -- Review of the Approaches and Modeling Methodology for Lithium-ion Battery Thermal Management Systems in Electric Vehicles -- Failure Criteria for Composite Blades with Wavy Edge in Aerospace Applications -- Stress and Deformation Analysis of Hip Joint for Design of Hip Prosthesis.
Electronic reproduction
Keywords: Electronic books. Materials -- Congresses; Mechanical engineering -- Congresses